Analyzing the influence of varied fuel injection pressure on diesel engine fueled with Karanja biodiesel. (2020) - Karikalan, L.; Jacob, S.; Baskar, S.; Venugopal, S.
Abstract: Performance and pollutants of diesel engines largely rest on factors like fuel injection pressure, number of injections, fuel quantity injected, state of injection, combustion chamber design and nozzle spray patterns. The intention of this effort is to evaluate the diesel engine performance and pollutant features by changing the biodiesel fuel injection pressures. Based on these, the features such as BTE, SEC, CO, HC, NOX and smoke emissions in exhaust were recorded. The results show that the biodiesel can be utilized as substitute fuel successfully in a CI engine at optimum fuel injection pressure with no major engine alteration.